Ionic conductive gels based on deep eutectic solvents. Issue 3 (3rd July 2021) - Liu, Cuiping; Qi, Jinfan; He, Bingbing; Zhang, Huan; Ju, Jie; Yao, Xi
ABSTRACT: Ionic conductive gels are promising soft conductors for stretchable and flexible electronics. Unfortunately, the basic requirements for an ideal ionic conductive gel, including environmental and chemical stability as well as low toxicity and low cost do not usually coincide in one material. Here we report an ionic conductive gel containing deep eutectic solvents (DES), which are specialized ionic liquids composed of propylene glycol (PG, hydrogen bonding donor) and various salts. In experiments, the DES-gel loses about 10% of the original weight in dry air (5– 9% relative humidity) for 7 days and its conductivity remains unaltered. Comparing to regular salt-containing hydrogels, it exhibits exceptional resistance to metal corrosion. We demonstrate the advantage of DES-gels as the ionic electrode in a flexible and stretchable electroluminescent device, especially in cold environment (−20°C). Through this study, we discover a new candidate for cheap and safe soft ionic conductors with excellent environmental and chemical stability. Graphical abstract: uf0001